2018
DOI: 10.20885/ejem.vol10.iss2.art1
|View full text |Cite
|
Sign up to set email alerts
|

Decomposed total factor productivity of Indonesian rice production

Abstract: This paper analyzes the growth of total factor productivity of paddy farming efforts. Total productivity is decomposed into four parts: the advancement of technology, technical efficiency, allocative efficiency and the effect of business scale. If each component of productivity growth is known, strategies to increase rice production can be determined. This paper uses secondary data published by the Indonesian Statistics Agency. The analyses were performed using an econometric approach. The results show that gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Therefore, sectoral technical change constitutes technological advancement and knowledge transfer and by implication TFP. Empirically, different works of literature (For example, Plastina and Lence (2018); Jajri (2007); Mariyono (2018); Mastromarco and Zaglo (2012)) have concluded that technological advancement is the largest contributor for the change in TFP and TFP growth rate.…”
Section: Model Estimation Techniquementioning
confidence: 99%
“…Therefore, sectoral technical change constitutes technological advancement and knowledge transfer and by implication TFP. Empirically, different works of literature (For example, Plastina and Lence (2018); Jajri (2007); Mariyono (2018); Mastromarco and Zaglo (2012)) have concluded that technological advancement is the largest contributor for the change in TFP and TFP growth rate.…”
Section: Model Estimation Techniquementioning
confidence: 99%
“…In Indonesia, the agriculture sector contributes over 13% of Gross Domestic Product, second largest after manufacturing sector. Rice is important as a staple food and represents the highest calorie intake for more than 250 million people (Mariyono, 2018).…”
Section: Indonesiamentioning
confidence: 99%
“…In this income distribution process, there will be a cycle (turnover) where consumers have to pay the price of the goods. On the other hand, consumers also become the provider of capital, labor, natural resources, or expertise so that besides paying the price of the goods, they will receive a share of income at certain times (Maryono, 2018). In the production process, each provider of production factor will receive a service compensation as follows: (1) Owners of natural resource factors (land) will receive land rent, (2) Owners of labor factors will receive wages, (3) Owners of capital will receive capital interest, and (4) Entrepreneurs will receive operating profits.…”
Section: Literature Reviewmentioning
confidence: 99%